Social participation and mortality according to company size of the longest‐held job among older men in Japan: A 6‐year follow‐up study from the JAGES. Issue 1 (31st March 2021) - Kanamori, Satoru; Kondo, Naoki; Takamiya, Tomoko; Kikuchi, Hiroyuki; Inoue, Shigeru; Tsuji, Taishi; Kai, Yuko; Muto, Go; Kondo, Katsunori
Abstract: Objectives: The purpose of this study was to examine the relationship between social participation (type/pattern) and mortality according to company size of the longest‐held job among older men in Japan who have worked in the company. Methods: Longitudinal data from the Japan Gerontological Evaluation Study were used in this study. Functionally independent individuals aged 65 years and older in Japan were surveyed. Work and community organizations (local community, hobbies, and sports) were used as social participation. A Cox proportional hazards model was used to calculate mortality hazard ratios. Results: Analysis was carried out on 19 260 participants. A total of 2870 deaths occurred during the 6‐year follow‐up period. Those in companies with 49 or fewer employees had the highest prevalence of work participation and the lowest participation in any community organization. Regardless of company size, the mortality risk was significantly lower for participants in any social participation (eg, the hazard ratio for participation in a hobby organization among those with a company size of 49 employees or fewer was 0.74, 95% CI: 0.65‐0.85) compared to nonparticipants whose company size was 49 or fewer employees. Conclusions: In Japan, although older men who have worked for small companies may have fewer benefits, their social participation may reduce their mortality risks. To avoid increasing health inequalities, it is necessary to create an environment in which they are more likely to participate in social activities.